Neonatal Transport - Review Article - R. Abhilasha Singh Panwar; Sachin Damke (Institute of Medico-legal Publications Pvt Ltd, 2021)
Various factors lead to neonatal mortality, in which transport of neonates play an important role in mortalityand morbidity of neonates. In India neonatal transport has not developed well. Many sick neonatessuccumb during transport or become very serious during transport. Transport duration, type of transport,treatment given during transport , if pretransport treatment received, maintenance of hemodynamic stability,maintenance of temperature and blood sugars during transport is essential for reducing the mortality of thebaby. Regionalizing neonatal care, will help in deciding the transport of neonates from one centre to anhigher level of care. Hence a well-organized transport system should be in place for the transport of the sickneonates. This review article discusses about the neonatal transport and its implications.